The nexuses between budget deficit and price inflation in Pakistan: An ARDL bound testing approach - Sulaiman D. Muhammad; Saba Zafar; Muhammad Noman; Najamul Arfeen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Fiscal imbalances are one of the common economic indicators of developing countries as these countries have a structural weakness on one hand and a strong desire to invest in capital intensive projects that speeds up the pace of development. It has been noticed that in the last couples of years price expansion has slowed down and falling crude oil prices have been the most important factor in slow down price expansion. This study explores the association between inflation and indicators of fiscal imbalances in the first place and second how the choice of financing fiscal imbalances influences price expansion. To explore this connection, a time series data of Pakistan span from 1973 to 2014 have been employed. Different methods of financing fiscal imbalances have been followed, including borrowings and printing of money. The observational discoveries of the paper depict that there is a direct association between inflation and indicators of fiscal imbalances. Every method of financing imbalances is directly and essentially identified with the price expansion within Pakistan. The ARDL bound testing approach is employed to test this relation. Government has to take care of the problem of fiscal imbalances before it becomes more severe and serious.
Keywords: 330; budget deficit; government borrowing; exchange rate; money supply; inflation